2015
DOI: 10.1109/lpt.2015.2421950
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Memory Effect in Polymer Optical Fibers

Abstract: The basic properties of a "thermal memory effect" of polymer optical fibers (POFs) are experimentally investigated. We measure the thermally induced loss as a function of time at several high temperatures, and find that the loss becomes almost constant after heating for ~200 s. The loss remains unchanged even after the heated section is cooled to room temperature. We subsequently measure the optical time-domain reflectometry traces under three different conditions: (1) before a POF section is heated, (2) short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Until the 2000s, FBG sensors were maturely fabricated into standard optical sensors by using various techniques, including phase mask, pico-, and femtosecond laser inscription, and interferometric setting [15][16][17]. Recently, Bragg grating fabrication based on various materials or special fiber structure design is emerging rapidly [18][19][20][21], for instance, a chirped Bragg grating on microstructured polymethyl methacrylate fiber proposed by Korganbayev et al (2018) [22] that demonstrated excellent sensitivity for thermal profile detection; and some multicore fibers (MCFs) have been used as fiber optic three-dimensional shape sensors such as the helical MCF with continuous grating developed by Lally et al (2012) [23] for real-time shape sensing using the optical frequency domain reflectometry technique. Such sensors have been widely applied in civil engineering [24], healthcare medical devices [25,26], structural engineering [27,28], aerospace [29], oil and fuels [30], and harsh environments [31], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Until the 2000s, FBG sensors were maturely fabricated into standard optical sensors by using various techniques, including phase mask, pico-, and femtosecond laser inscription, and interferometric setting [15][16][17]. Recently, Bragg grating fabrication based on various materials or special fiber structure design is emerging rapidly [18][19][20][21], for instance, a chirped Bragg grating on microstructured polymethyl methacrylate fiber proposed by Korganbayev et al (2018) [22] that demonstrated excellent sensitivity for thermal profile detection; and some multicore fibers (MCFs) have been used as fiber optic three-dimensional shape sensors such as the helical MCF with continuous grating developed by Lally et al (2012) [23] for real-time shape sensing using the optical frequency domain reflectometry technique. Such sensors have been widely applied in civil engineering [24], healthcare medical devices [25,26], structural engineering [27,28], aerospace [29], oil and fuels [30], and harsh environments [31], among others.…”
Section: Introductionmentioning
confidence: 99%
“…rillouin scattering in optical fibers has been the subject of extensive research owing to its capability of distributed measurement of strain and temperature. [1][2][3][4][5][6][7][8][9][10][11][12] To date, glass optical fibers have mainly been used for the sensor heads of Brillouin sensors, but in order to enhance the flexibility (i.e., strain dynamic range), some research groups [13][14][15][16][17][18][19][20][21][22] have started to employ polymer optical fibers (POFs) as the sensor heads. One report has proven that sometimes POFs can withstand extremely large strains of more than 100%.…”
mentioning
confidence: 99%
“…One report has proven that sometimes POFs can withstand extremely large strains of more than 100%. 13) POF-based sensors have another unique feature called strain and thermal "memory" functions, 14,15) with which the information on the applied large strain (or overheat) can be stored owing to their plastic deformation. For instance, if we exploit the strain memory function, we can propose a novel concept: "we need not always place expensive analyzers at the ends of the sensing fibers; after earthquakes, an officer has only to go round with a single interrogator".…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] In 2010, Brillouin scattering in polymer optical fibers (POFs) was observed for the first time; 19) since then, several research groups have been developing POF-based Brillouin sensors [20][21][22][23] with large-strain measurability, 24) greater ease of handling, and the so-called memory functions of strain 25) and temperature. 26) Unlike the other groups studying POFbased Brillouin sensing with two-end-access configurations (Brillouin optical time-domain analysis 20) and Brillouin optical frequency-domain analysis 21) ), we have been in the process of developing POF-based single-end-access distributed sensing systems, using a unique technique called Brillouin optical correlation-domain reflectometry (BOCDR). 17,18) In addition to the single-end accessibility, the advantages of BOCDR include high spatial resolution, random accessibility, and cost efficiency.…”
mentioning
confidence: 99%